2009
DOI: 10.1088/0004-637x/706/2/1309
|View full text |Cite
|
Sign up to set email alerts
|

CASTING LIGHT ON THE “ANOMALOUS” STATISTICS OF Mg II ABSORBERS TOWARD GAMMA-RAY BURST AFTERGLOWS: THE INCIDENCE OF WEAK SYSTEMS

Abstract: We revisit echelle spectra (spectral resolution R ≈ 40 000) of 8 Gamma-Ray Burst afterglows to obtain the incidence (dN/dz) of weak intervening Mg II systems at a mean redshift of z = 1.5. We show that dN/dz of systems having restframe equivalent widths 0.07Å ≤ W MgII r < 1Å toward GRBs is statistically consistent with the incidence toward QSOs. Our result is in contrast to the results for Mg II systems having W r ≥ 1Å, where dN/dz toward GRBs has been found to be larger than toward QSOs by a factor of ≈ 4. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 39 publications
5
33
0
Order By: Relevance
“…Since both GRBs and quasars probe intervening material randomly, it was a puzzling discovery a decade ago that GRBs apparently had four times as many strong intervening Mg ii absorbers with rest-frame equivalent widths W λ2796 r > 1 Å as did quasars (Prochter et al 2006b). The same conclusion about Mg ii absorber statistics was reached by Sudilovsky et al (2007), with the addition that the incidence rate of C iv absorbers and weak Mg ii absorbers with W r < 1 Å did agree between the two background source types (Tejos et al 2007(Tejos et al , 2009Vergani et al 2009). Also blazars were found to have twice as many strong Mg ii absorbers as did quasars (Bergeron et al 2011).…”
Section: Introductionsupporting
confidence: 61%
“…Since both GRBs and quasars probe intervening material randomly, it was a puzzling discovery a decade ago that GRBs apparently had four times as many strong intervening Mg ii absorbers with rest-frame equivalent widths W λ2796 r > 1 Å as did quasars (Prochter et al 2006b). The same conclusion about Mg ii absorber statistics was reached by Sudilovsky et al (2007), with the addition that the incidence rate of C iv absorbers and weak Mg ii absorbers with W r < 1 Å did agree between the two background source types (Tejos et al 2007(Tejos et al , 2009Vergani et al 2009). Also blazars were found to have twice as many strong Mg ii absorbers as did quasars (Bergeron et al 2011).…”
Section: Introductionsupporting
confidence: 61%
“…These authors found that nearly every GRB sightline exhibits at least one absorber ( z = 1.1) whereas the incidence of strong Mg ii QSO absorbers is about four times smaller. This excess is confirmed by Sudilovsky et al (2007) for a small, homogeneous sample of GRB VLT-UVES high-resolution spectra, and more recently by Tejos et al (2009) and Vergani et al (2009). Based on their improved statistics, these latter authors find the excess to be smaller than initially reported, by a factor of 2.1 ± 0.6 instead of ∼4.…”
Section: Introductionmentioning
confidence: 53%
“…One of the strong system given in Table 2 is excluded (northern blazar) since the low S /N prevents detection of weak systems. We thus get: The errors are based on Poisson statistics for small numbers with limits corresponding to 1σ confidence level of a Gaussian distribution as tabulated by Gehrels (1986) and also adopted by Tejos et al (2009). To compare this value to the incidence of Mg ii absorbers measured along QSO sight lines, we use the incidence of these systems per unit redshift derived from SDSS data.…”
Section: Global Excessmentioning
confidence: 99%
“…Cucchiara et al (2009) compare properties of foreground Mg ii systems along quasar and GRB sightlines and find no significant differences, concluding that the GRB systems are probably not associated with material ejected near the GRB at relativistic velocities (intrinsic origin). Tejos et al (2009) and Vergani et al (2009) also study the incidence of weak Mg ii systems, and both come to the conclusion that the incidence of weak systems is similar along quasar and GRB afterglow sightlines, implying that the best explanation is that the GRB afterglows of the echelle sample have been amplified by gravitational lensing (see also Wyithe et al 2010, but see Cucchiara et al 2009). Both studies also find that the excess is smaller than originally deduced from the original small sample by Prochter et al (2006), but the significance that the excess is real has increased with increasing sample size and redshift path.…”
Section: Does the High Number Of Mg II Foreground Absorbersmentioning
confidence: 96%
“…All GRBs in the UVES sample of Vergani et al (2009) are included in our Golden Sample (with GRB 021004 being part of the pre-Swift Golden Sample, and GRB 060607A not having any data at 0.5 rest-frame days, so we will not include it in this discussion), and two further GRBs with echelle spectra (Keck HIRES) from the sample of Tejos et al (2009) are also part of our Silver Sample. Furthermore, a GRB with published UVES spectroscopy not included in the sample of Vergani et al (2009) is XRF 080330, which also shows a very strong Mg ii foreground absorber (D'Elia et al 2009b), and another strong foreground system is seen in the afterglow of GRB 090313, as measured by X-Shooter (de Ugarte Postigo et al 2010).…”
Section: Does the High Number Of Mg II Foreground Absorbersmentioning
confidence: 99%